The Influence Of Reconstitution Vehicles On The Stability Of Ampicillin Oral Powders - YOUSIF, M A.; FAROUK, A. (Gezira Journal of Health Sciences, 2003)
The effect of different reconstitution vehicles on the stability of ampicillin oral powders was studied. Distilled water, tap water and well water were used for powder reconstitution. The suspensions were stored at 35 0 C that representing the average room temperature in Sudan. The stability of the  drug in suspension was tested daily over a period of seven days. The drug contents in the samples were determined using the cup- plate agar diffusion technique and chemical spectrophotometric method. The obtained results, represented the means of 10-20 determinations. The study revealed a higher degradation extent in the  ampicillin oral powders reconstituted with water obtained from wells, followed by tap water  when compared with the slower rate of degradation in the oral antibiotic that reconstituted with distilled water.  In an attempt to decrease the destabilizing effect of the reconstitution vehicles on the daily used oral antibiotic powders, the authors suggested to use such formulae in a single-dose sachet form to be used instantly after reconstitution.